Jenis-Jenis Gastropoda di Zona Intertidal Pantai Indrayanti Yogyakarta - Dian Fita Lestari; Fatimatuzzahra Fatimatuzzahra; Syukriah Syukriah (Journal of Science and Applicative Technology, 2021)
Gunung Kidul is one of the districts in Yogyakarta that has a long coastline with coral substrate and white sand. One of the beaches with coral and rocky substrates is Indrayanti Beach. The rocky substrate provides unique characteristics for the life of marine organisms in the intertidal zone. Gastropods is one of the seven classes in the Mollusc phylum. Gastropods are found mostly in the sea and fresh water, especially in the intertidal zone of beach. The aim of this study is to identify gastropods that found in the Indrayanti intertidal zone and classifying each species. The method of this study is observation and sampling techniques with accidental sampling at low tide. Data analysis is descriptive based on morphological characteristics of each species. Based on the results of this study, there are 5 sub-classes, 9 orders, 2 Superfamily, 21 families, 35 genera and 72 species. Sub-classes found are heterobranchia, caenogastropods, neritimorpha, vestigastropods, and patelogastropods. The highest number of species found in the caenogastropod subclass was 32 species (44% of the total species) which were dominated by the order of neogastropod.